A solid-state circuit breaker for DC system using series and parallel connected IGBTs. (July 2022) - Xi, Jiawen; Pei, Xiaoze; Niu, Liyong; Feehally, Tom; Wilson, Peter; Gu, Chenghong; Zeng, Xianwu
Abstract: MVDC systems have attracted a lot attention for the integration of renewable energy and electrification of transport due to their superior system operational performance and high power quality. DC circuit breakers are of significant importance for the development of MVDC systems because they offer fast protection from fault conditions compared to mechanical equivalent. However, unlike AC systems, there is no zero-crossing for the current in DC systems, this makes the DC circuit breakers design more demanding. This paper presents the design of a solid-state DC circuit breaker (SSCB) in details using series and parallel configurations of IGBTs to increase the voltage and current ratings. The operation, electrical design and thermal design of the SSCB are presented and analysed. A PLECS model is developed to simulate the operation of the SSCB. A 1 kV SSCB prototype is built and experimentally tested under both static and dynamic conditions. The prototype demonstrates even current sharing and voltage balancing in the experimental tests. The prototype can carry 150 A current continuously without overheating and demonstrates successful interruption of 1 kA DC current. Highlights: Solid-state circuit breaker using series and parallel configurations of IGBTs. Thermal design through theoretical analysis, modelling, and testing. Solid-state circuit breaker experimentally tested in static and dynamic conditions. The prototype demonstrated successful interruption of 1 kA direct current.